THE IMPLEMENTATION OF RECEPTION-ORIENTED CAM WITH WORKSHEETS TO IMPROVE GRADE 10 STUDENTS’ CONCEPTUAL UNDERSTANDING OF QUADRATIC EQUATIONS AND FUNCTIONS IN A CHRISTIAN SCHOOL - Astuti, Dea Dri; Hidayat, Dylmoon (JOHME: Journal of Holistic Mathematics Education, 2020)
Based on observations and summative test results, the researcher identified that students' difficulties in learning quadratic equations and functions was conceptual understanding. Conceptual understanding enables students to analyze, integrate, and apply a concept in different situations. The purpose of the research was to see if the implementation of the Reception-Oriented CAM with worksheets improved students’ conceptual understanding and to find an effective way to implement the method. The researcher used a two-cycle Classroom Action Research of Pelton’s with seven grade 10 female students at a Christian school in Tangerang as the research subjects. Data was collected by test sheets, observation sheets, feedback sheets, and documentation. The result showed that the Reception-Oriented CAM with worksheets could improve students’ conceptual understanding in learning quadratic equations and functions. Another result showed that an effective way to implement Reception-Oriented CAM with worksheets was through implementing all the phases of the method thoroughly by giving more time in phase three and giving detailed instruction to the students. BAHASA INDONESIA ABSTRACT: Berdasarkan pengamatan dan hasil tes sumatif, peneliti mengidentifikasi bahwa kesulitan siswa dalam belajar persamaan dan fungsi kuadrat adalah dalam memahami konsep. Pemahaman konsep memungkinkan siswa untuk menganalisis, mengitegrasi, dan menerapkan konsep dalam berbagai situasi. Tujuan penelitian ini adalah untuk melihat manfaat penggunaan Reception Oriented CAM dengan lembar kerja untuk meningkatkan pemahaman konsep dan menemukan suatu cara yang efektif dalam penerapan metode tersebut. Penelitian tuindakan kelas dua siklus dengan model Pelton ini mengambil subyek tujuh siswi kelas 10 di suatu Sekolah Kristen di Tangerang. Data dikumpulkan dengan lembar tes, observasi, lembar umpan balik, dan dokumentasi. Hasil penelitian menunjukkan bahwa metode Reception Oriented CAM dengan lembar kerja dapat meningkatgkan pemahaman konsep siswa dalam pembelajaran persamaan dan fungsi kuadrat. Hasil penelitian juga menunjukkan bahwa cara yang efektif untuk menerapkan Reception Oriented CAM dengan lembar kerja adalah dengan cara memberikan waktu yang cukup pada langkah ke tiga dan memberikan instruksi dengan detail kepada siswa-siswa sebelum pembelajaran dimulai.